Ответы и объяснения

  • irakim
  • почетный грамотей
2013-04-29T22:53:35+04:00

D=144-4*32=16

x1=(12-4)/2=4

x2=(12+4)/2=8

 

по формуле, т.к. ax^2+bx+c=0  => a(x-x1)(x-x2)

 

(x-8)(x-4)=(x-8)(x-4)

тождество доказано

  • Участник Знаний
2013-04-29T22:55:22+04:00

x^2-12x+32=(x-8)(x-4)

правая часть: (x-8)(x-4)=x^2-4x-8x+32=x^2-12x+32 

x^2-12x+32=x^2-12x+32, чтд.

 

Можно доказать, используя правую часть

x^2-12x+32=0

\left \{ {{x1+x2=12} \atop {x1*x2=32}} \right.\left \{ {{x1=4} \atop {x2=8}} \right.

x^2-12x+32=(x-4)(x-8)

(x-4)(x-8)=(x-8)(x-4, чтд